Answer to Question equation-1

For reference, here is the equation that we must show is false.
  cat(h:t, u:v) = h:(u:(cat(t, v)))
There are many counterexamples. How about h = 1, t = [2], u = 3 and v = [4]. The left-hand side of the equation is
  cat(1:[2], 3:[4]) = cat([1,2], [3,4])
                    = [1,2,3,4].            from the definition of what cat does
The right-hand side of the equation is
  1:(3:(cat([2], [4]))) = 1:(3:([2,4]))     from the definition of cat
                        = 1:[3,2,4]         since 3:[2,4] = [3,2,4]
                        = [1,3,2,4]         since 1:[3,2,4] = [1,3,2,4]
The two sides are not the same for this example. So they are certainly not always the same.